DAMPAK KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) DARURAT TERHADAP REAKSI PASAR SAHAM SEKTOR KESEHATAN (HEALTHCARE) PADA BURSA EFEK INDONESIA: SEBUAH PENDEKATAN EVENT STUDY - Kezia Gabrielle; Shofwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to examine the information content contained in the announcement of the emergency Community Activity Restrictions policy announcement on July 1, 2021 which was carried out by analyzing abnormal returns and trading volume of healthcare sector activity in the period surrounding the event. This research is a quantitative research with an event study approach. The data analysis tool used to test the hypothesis in this study is the one sample T-test statistical test on the abnormal return indicator and the Paired sample t-test on the trading volume activity indicator. The results of the t-test indicate that there is a positive abnormal return on the main board stocks, thus proving that the market responds to the event as good news. Meanwhile, on the development board stock, there is an abnormal return that has a negative value, thus proving that the market responded to the event as bad news. It can be concluded that the healthcare sector stock market responds to the emergency PPKM announcement differently according to the characteristics of the stock listing board. The results of the different Paired Sample T-test on the average trading volume activity (ATVA) indicator before and after the emergency PPKM announcement show that there are differences in ATVA on the main board and development board stocks. This difference may be caused by the behavior of investors who sell or buy stocks in the health sector based on the category of the stock listing board